Evaluating phosphorus availability from sewage sludge derived pyrochar and hydrochar on spring wheat - Pimenta Da Costa Ocampo, Maria (Cranfield University, 2021)
The production of sewage sludge is expected to increase as the population continuously develops worldwide. Being a source of nutrients, the re-use of this material as soil amendment could address the current unstable situation. Sewage sludge could be an alternative source of available phosphorus to chemical fertilisers that could help to remediate the growing demand of mineral phosphorus reserves. In parallel, it also acts as a good source of organic matter for low fertile soils resulting from overexploitation and erosion events. Even though recent studies have been focusing on the use of sewage sludge on land application, there is still a stigma attached to this practice as its use in agriculture has to be managed carefully due to its variability in physical-chemical properties. The perception of sewage sludge as a source of pollutants relies on current research and it´s tampered by the huge diversity of feedstocks and the variability of it depending on the sampling. Thermal treatments are assessed as route towards the production of alternative P fertilisers from sewage sludge. Two pyrochars were produced though pyrolysis at 400⁰C (P400-1) and 300⁰C (P300-1) for 1h using pre-oven dried (105⁰C-48h) sewage sludge from Spain (SSES). Two hydrochars were obtained through Hydrothermal Carbonization at 180⁰C (H180-4) and 240⁰C (H240-4) for 4h, using SSES adjusted to 20% dry matter. P availability changes of SSES were evaluated after thermal treatments and its effect on soil available P content when added on their own (5, 10, 20 t ha⁻¹) and in combination with a commercialized sewage sludge from UK (SSUK) as soil amendment (50% char 50% SSUK, at 10, 20, 40 t ha⁻¹). Single and combined amendment were carried out at the same time, comprising a total of 136 pots (H:50 cm; D:10.5 cm). Thermal treatments reduced available-P in all derivatives H180-4 (45.9%), H240-4 (57.5%), P300-1 (76.2%), P400-1 (83.6%) from 150.4 mg kg⁻¹SSES. Nonetheless, one single application over two cropping seasons of spring wheat in a glasshouse increased available-P to 23.7-26.7 mg kg⁻¹ from 1.5 mg kg⁻¹in control soil when combined at 40 t ha⁻¹. No significant improvement was observed in grain yield over two seasons among the treatments, but the nutrient balance and heavy metals assessment indicated an evolution of these materials in the soil over time. The use of pyrochars, produced a buffering effect that lasted two seasons preventing an acidification of the loamy sandy soil that couldn’t be achieved though hydrothermal carbonisation. This study shows the potential of thermal treatments as pre-treatment, and its limitations. Sewage sludge in agriculture must be managed carefully due to its variability in physical-chemical properties and their content of Al, Fe and heavy metals. Acidification of the soil should be avoided in order to obtain better results on P availability. Pyrolysis of sewage sludge may not replace mineral fertilisers, but it could be used to prevent acidification if used as a pre-treatment of sewage sludge, increasing carbon stability and organic matter in loamy sandy soil, immobilizing heavy metals, and providing a slow release of P.
Keywords: Sewage sludge; hydrothermal characterisation; pyrolysis; hydrochar; pyrochar; alternative fertilisers; soil analysis; heavy metal environment risk; phosphorus use effieciency; phytotoxicity on seed germination; grain yield